Structural, functional, and symptom relations in painful distal symmetric polyneuropathies: a systematic review. Issue 2 (February 2019) - Karlsson, Pall; Hincker, Alexander M.; Jensen, Troels Staehelin; Freeman, Roy; Haroutounian, Simon
Abstract : Abstract: The diagnosis of distal symmetric polyneuropathies (DSPs) relies on the presenting symptomatology and neurological sensory examination, supported by objectively quantified structural and functional changes in sensory nerves. Although these separate components have important diagnostic utility, the associations between the structural vs the symptomatic and functional findings in painful DSP are still unclear. It is assumed that delineation of the correlations, or lack of such, between structure, clinical presentation, and function will contribute to a better understanding and treatment of DSP. This systematic review assessed small fiber morphology in patients with different types of painful DSP, and compared it with symptoms, signs, and nerve fiber function. Overall, 111 papers met the inclusion criteria for the systematic review. The results indicate that epidermal nerve fiber loss, in isolation, is not a useful indicator of painful symptoms or their severity in DSP. Intraepidermal nerve fiber density correlated reasonably well with neuropathy scores on tools assessing signs and symptoms (such as the Michigan Neuropathy Screening Instrument and the Total Neuropathy Score), but less so with symptom measures only. Among various psychophysical sensory measures, warmth detection and heat pain thresholds correlated best with intraepidermal nerve fiber density, particularly when assessed at the same anatomical site. The observed sources of heterogeneity, and the lack of associations between structural and functional measures in several studies are discussed. A framework is proposed for uniform assessment of nerve fiber parameters for investigating clinically relevant mechanisms of neuropathic pain in DSP. Abstract : Supplemental Digital Content is Available in the Text.